"Success by Association": The Impact of Venture Capital Firm Reputation Trend on Initial Public Offering Valuations. (February 2021) - Chahine, Salim; Filatotchev, Igor; Bruton, Garry D.; Wright, Mike
Organizational theory recognizes reputation as a central element to understanding the firm. Examining investor valuations of 1, 676 initial public offerings (IPOs) in the United States from 1990 to 2011, we find that reputation transfer through an association of an IPO firm with a venture capital (VC) firm represents a resource whose value can increase/decrease over time depending on investors' valuations of prior IPOs funded by a VC firm. We conclude that the impact of reputation transfer through association is not unidirectional but, instead, is to be viewed in the context of prior reputational development of organizations the focal firm is associated with. Furthermore, we find that three "transfer enhancers" can improve the impact of VC firm reputation transfer on IPO valuations, including the VC firm's past experience intensity, the diversity of IPO experiences, and the number of prior syndicated IPOs involving the VC firm as a lead investor.